MAPPING OF SOIL DEGRADATION POTENCY IN PADDY FIELD WONOGIRI, INDONESIA - Mujiyo Mujiyo; Rahayu Rahayu; Reni Ustiatik; Dhika Sri Anggrahini (Sains Tanah - Jurnal Ilmu Tanah dan Agroklimatologi, 2016)
Sustainability of paddy field becomes the main concern as the media of biomass production, thus it is needed a data and information about land characteristics to find out its degradation. Mapping of soil degradation potency in paddy field is an identification of initial soil condition to discover the land degradation potency. Mapping was done by overlaying map of soil, slope, rainfall and land use with standard procedures to obtain its value and status of soil degradation potency. Area mapping is an effective land for biomass production (natural forest, mixed farm, savanna, paddy field, shrub and dry field) with approximately 43,291.00 hectares (ha) in Sidoharjo, Girimarto, Jatipurno, Jatisrono, Jatiroto, Tirtomoyo, Nguntoronadi and Ngadirojo District. The result shows that soil degradation potency (SDP) in Districts of Sidoharjo, Girimarto, Jatipurno, Jatisrono, Jatiroto, Tirtomoyo, Nguntoronadi and Ngadirojo are very low (DP I) 0.00 ha (0.00%), low (DP II) 20,702.47 ha (47.82%), moderate (DP III) 15,823.80 ha (36,55%), high (DP IV) 6,764.73 ha (15.63%) and very high (DP V) 0.00 ha (0.00%). Paddy field is 22,036.26 ha or about 50.90% of all area as effective biomass production, its SDP considers as low (DP II) 16,021.04 ha (37.01%) and moderate (DP III) 6,015.22 ha (13,89%). Paddy field has a low SDP because it is commonly lies on flat area and conservation method by the farmer is maintaining the paddy bund and terrace. This study needs an advanced study to identify actual SDP through detail verification in the field, and also support by soil sample analysis in the laboratory.